Experimental Investigation Of Performance And Emissions Of A Stratified Charge CNG Direct Injection Engine With Turbocharger - Amiruddin, Hilmi; Wan Mahmood, Wan Mohd Faizal; Abdullah, Shahrir; Mansor, Mohd Radzi; Abdollah, Mohd Fadzli (EDP Sciences, 2017)
This paper presents the results from 1.6 litre, 4 cylinders stratified charge compressed natural gas (CNG) direct injection engine with boosting device. A turbocharger with compressor trim of 40 was used to increase engine output. The engine was tested at wide open throttle (WOT) and speed ranging from 1000 to 5000 rpm. Engine performance and emissions data were recorded under steady state condition. Results show turbocharged CNG engine produced an average of 26% increment in brake power and 24% additional maximum brake torque as compared with natural aspirated (NA) CNG engine. Turbocharged CNG engine improved brake specific fuel consumption (BSFC) and yielded higher fuel conversion efficiency (FCE). Relatively turbocharged CNG engine showed lower emission of hydrocarbon (HC) and carbon monoxide (CO) throughout tested engine speed. Conversely, the carbon dioxide (CO2) and nitrogen oxide (NOx) emission produced were slightly higher compared with NA CNG engine.